189 IMPROVING DEMENTIA CARE THROUGH SELF-EXPERIENCE; CO-DESIGNING A SIMULATION-BASED DEMENTIA EDUCATION TOOLKIT. (25th October 2022) - Collins, R; Forristal, K; Hopper, L; Riello, M; Conotter, V; Meyer, G; Vugt, MD
Abstract: Background: Although specialised dementia education programmes have begun to appear in recent years, they lack consistency. Knowledge gaps persist, which results in a professional workforce who can struggle to anticipate the care needs of people with dementia. Self-experience or simulation practices (e.g., roleplays, virtual reality, sensory tools) are established teaching methods that can provide learning opportunities to experience aspects of illness. These innovative learning approaches can positively impact empathy, understanding, and quality of care; however, they are rarely implemented in specialised care for people with dementia. The Improving demeNtia care Through Self-Experience (INTENSE) project has co-designed a dementia simulation toolkit to educate, equip, and train professionals to better support people with dementia. Methods: As part of the Erasmus+ INTenSE project, a series of three participatory, online workshops were conducted with people with dementia, informal caregivers, and dementia-care professionals in Ireland, Italy, Germany, and the Netherlands. The first explored the co-design of training scenarios using simulation tools to demonstrate the lived experience of dementia. The second involved the co-design of an online training platform. The third examined the sustainable implementation of INTenSE into practice. All workshops were inductively coded and analysed thematically. Results: Recommended training scenarios demonstrate daily activities and environments that impact people with dementia using a combination of existing and newly developed simulation tools. Four themes arose from workshop discussions: 1) representation of dementia, 2) daily challenges that impact people with dementia, 3) applying a person-centred approach, and 4) implementing self-experience training. Together these were used to develop facilitation guides to support the implementation of the INTenSE simulation toolkit into practice. Conclusion: These findings demonstrate the potential of simulating self-experience across a range of everyday scenarios as a means to increase professionals' empathy and understanding of the lived experience of dementia. Recommendations have been developed that support the use of self-experience tools in practice.